2011
DOI: 10.1016/j.ydbio.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Blastema induction in aneurogenic state and Prrx-1 regulation by MMPs and FGFs in Ambystoma mexicanum limb regeneration

Abstract: Urodele amphibians can regenerate amputated limbs. It has been considered that differentiated dermal tissues generate multipotent and undifferentiated cells called blastema cells during limb regeneration. In early phases of limb regeneration, blastema cells are induced by nerves and the apical epithelial cap (AEC). We had previously investigated the role of neurotrophic factors in blastema or blastema-like formation consisting of Prrx-1 positive cells. A new system suitable for investigating early phases of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 69 publications
(107 reference statements)
2
90
0
Order By: Relevance
“…Although it has been found that application of Gdf5 and Fgfs can induce limb formation in an accessory limb model of axolotl regeneration (Satoh et al, 2011), this is the first example to our knowledge of a single protein rescuing regeneration in the denervated axolotl limb. These results suggest that NRG1 acts as an essential link between nerves and the blastema, as it promotes blastemal growth and proliferation throughout the entire process of limb regeneration, from early blastemal growth to later digit formation.…”
Section: Nrg1 Supplementation Rescues Regeneration In Denervated Limbsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although it has been found that application of Gdf5 and Fgfs can induce limb formation in an accessory limb model of axolotl regeneration (Satoh et al, 2011), this is the first example to our knowledge of a single protein rescuing regeneration in the denervated axolotl limb. These results suggest that NRG1 acts as an essential link between nerves and the blastema, as it promotes blastemal growth and proliferation throughout the entire process of limb regeneration, from early blastemal growth to later digit formation.…”
Section: Nrg1 Supplementation Rescues Regeneration In Denervated Limbsmentioning
confidence: 80%
“…Nerve dependence is a phenomenon observed during wound healing and regeneration across a wide range of phylogeny (Kumar and Brockes, 2012) and may be due to the secretion of essential growth-promoting factors from peripheral nerves at the wound site (Singer, 1952;Stocum, 2011). Though evidence has been gathered in support of numerous candidate factors, including transferrin (Kiffmeyer et al, 1991;Mescher et al, 1997), fibroblast growth factors (Satoh et al, 2011) and anterior gradient protein (Kumar et al, 2007), no neuronal factor identified thus far has proven capable of rescuing regeneration in the denervated axolotl limb. Here, we examined Neuregulin-1 (NRG1), a neuronally secreted mitogen that promotes proliferation through ErbB2 signaling (Falls, 2003b) and has been found in the newt peripheral nervous system (Brockes and Kintner, 1986) and implicated in newt limb regeneration (Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This protein is essential for limb bud skeletal patterning (Nohno et al., 1993). It is activated by dermal fibroblasts during blastema formation in the amputated axolotl limb and its expression is induced by MMP activity (Satoh, Makanae, Hirata, & Satou, 2011). …”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…A blastema is a population of pluripotent proliferating cells that can restore the lost parts of tissues. Signalling molecules, including TGFβ, Shh, Wnt, FGF, EGF and IGF, are expressed in the epidermis of the wound, and in some cases in blastema cells, to regulate the proliferation and differentiation of blastema cells via the MAPK cascade (Chera et al, 2011;Petersen and Reddien, 2009;Repiso et al, 2011;Satoh et al, 2011;Tasaki et al, 2011a;Tasaki et al, 2011b;Wang et al, 2009;Yazawa et al, 2009;Yoshinari and Kawakami, 2011). The activities of MAPKs are negatively regulated by MAPK phosphatases (Repiso et al, 2011;Tasaki et al, 2011a;Tasaki et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%